2018
DOI: 10.1002/pi.5507
|View full text |Cite
|
Sign up to set email alerts
|

A novel bio‐based phthalonitrile resin derived from catechin: synthesis and comparison of curing behavior with petroleum‐based counterpart

Abstract: The development of bio‐based thermosetting resins with good thermal stability can potentially afford sustainable polymers as replacements for petroleum‐based polymers. We report a practical route to a novel catechin‐based phthalonitrile resin precursor (CA‐Ph), which contains free phenolic hydroxyl groups that result in ‘self‐curing’ at elevated temperatures to afford a thermostable polymer. Comparison of the performance of this CA‐Ph resin with that of a conventional petroleum‐based bisphenol A phthalonitrile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Char yield was also comparable between the resins at above 70%. [158] An honokiol-derived resin showed a T m of below 70 °C and a T onset of around 230 °C, giving a good processing window and low onset of curing, again without the need for an additional curing agent (Figure 11). The melt viscosity of this resin and the magnolol resin studied were below that of an analogous petroleum resin, suggesting better resin infiltration characteristics.…”
Section: Sustainable Phthalonitrilementioning
confidence: 99%
“…Char yield was also comparable between the resins at above 70%. [158] An honokiol-derived resin showed a T m of below 70 °C and a T onset of around 230 °C, giving a good processing window and low onset of curing, again without the need for an additional curing agent (Figure 11). The melt viscosity of this resin and the magnolol resin studied were below that of an analogous petroleum resin, suggesting better resin infiltration characteristics.…”
Section: Sustainable Phthalonitrilementioning
confidence: 99%
“…21,25,46,70,72−74 In addition, a comparison of the melting points and biomass contents of biobased PN monomers of recent research is also shown in Figure S5. 7,33,42,75 The biomass content for all monomers takes only C and H into account. The results show that the VPN and IVPN resins with middle biomass content, in which biomethanol and pentaerythritol are not taken into account, 76 not only maintain excellent thermal properties but also have lower melting point.…”
Section: Thermal Stabilitiesmentioning
confidence: 99%
“…The activation energy EA of the matrix resin was higher than that of the ICA, which means the curing process of ICA is easier to take place. Therefore, the model equation of the unfilled matrix resin and self-made ICA can be described as Equations ( 7) and (8), respectively:…”
Section: Curing Kineticsmentioning
confidence: 99%
“…More importantly, it can be used to build the relationships among progress, time, and temperature, predict the shelf life for materials and products, estimate the decomposition of environmental pollutants, assess the risks, and provide the storage conditions for energetic materials [4][5][6]. Curing kinetics is a kind of phenomenological description of the reaction and is proven to be adequate to design and optimize a technical curing process or to investigate and differentiate the influences of resin/hardener types, catalysts, fillers, and additives, and thus is widely used [7][8][9][10]. The curing reaction of resin-based materials is an exothermic process and can be quantitatively studied by measuring the heat that is released, which is the foundation of curing kinetics analysis.…”
Section: Introductionmentioning
confidence: 99%